Perception towards impact of Corporations’ pay plans for part-time lecturers on service delivery in Kenya: A case of Public Universities - Ogembo, Paul Okeyo (Indonesian Journal of Economics, Social, and Humanities, 2025)
The swelling enrollment of students in the university programs and the nearly frozen teaching staff hiring in the universities lead to a gap in regular lecturers consequently calling for the faculties to outsource for part-time lecturers (PTLs). However, the plan for their remuneration remains elusive. The purpose of the study was to establish the perceptions towards impact of corporations’ pay plans for PTLs toward their service delivery. Specific objectives were to determine: whether there are any pay plans for PTLs by the public universities; nature of pay plans for PTLs and to establish level of satisfaction of PTLs with the universities’ pay plan and to establish level of satisfaction of with the universities’ pay plan. The study used critical literature review supported by Ferrer (1998). A theory of Social Justice underpinned the study. The study established that: there were letters of appointment without exact time of payment. That the question when will the payment be effected silently rested on availability of funds. That many a times delayed payments after marking and submitting scripts make the lecturers frustrated and that there was high level of dissatisfaction amongst PTLs with uncertainty of their pay by the universities, consequently affecting their teaching and research. The findings have implications on University management to properly plan for PTLs and quickly remunerate the. No study of that nature has been done in Kenya hence bridging knowledge gap and that it could help solve the problem of elusive remuneration of PTLs in Kenya.